Diseño de una turbina para una microcentral hidroeléctrica para la vereda Los Arrayanes en Viotá, Cundinamarca (2020)
In this work grade, the problem of the village of los arrayanes located in Viotá, Cundinamarca will be solved; As for the absence of the electric fluid, a situation that permanently affects its inhabitants and their quality of life through the design of a hydraulic turbine for a microcentral which will have a maximum power of 200 KW. Where the principle of operation of a hydroelectric micro-power plant and its impact on Colombia was analyzed and explained, an alternative of water supply and return to the channel was selected, through which it was evidenced how the fluid reaches the turbine and the actual flow to use.